2019
DOI: 10.12688/wellcomeopenres.15358.1
|View full text |Cite
|
Sign up to set email alerts
|

The negative health effects of hostile environment policies on migrants: A cross-sectional service evaluation of humanitarian healthcare provision in the UK

Abstract: Background: Recent UK ‘hostile environment’ immigration policies, including obligatory charging and sharing of confidential data between NHS Digital and the Home Office, have created an atmosphere of fear and exposed already highly marginalised and vulnerable groups to significant health risks by increasing barriers to accessing NHS care.  Methods:  This is a cross-sectional observational study of patients accessing healthcare at Doctors of the World (DOTW) in the UK. DOTW is a humanitarian organisation, provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…This is surprising given how understanding migrant healthcare access and experience is critical to planning health services and reducing barriers to access. Despite all residents in England regardless of immigration status being entitled to access primary care, a few studies showed that some migrants struggle to register with a General Practice, lack knowledge of their entitlement or even fear arrest when accessing NHS services ( Fang, 2015 ; Kang et al., 2019 ; Weller et al., 2019 ). In terms of secondary care where non-urgent treatment is chargeable for those who cannot prove their entitlement, research has shown that some migrants have been denied urgent care or received delayed treatment ( Potter et al., 2020 ; Doctors of the World 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising given how understanding migrant healthcare access and experience is critical to planning health services and reducing barriers to access. Despite all residents in England regardless of immigration status being entitled to access primary care, a few studies showed that some migrants struggle to register with a General Practice, lack knowledge of their entitlement or even fear arrest when accessing NHS services ( Fang, 2015 ; Kang et al., 2019 ; Weller et al., 2019 ). In terms of secondary care where non-urgent treatment is chargeable for those who cannot prove their entitlement, research has shown that some migrants have been denied urgent care or received delayed treatment ( Potter et al., 2020 ; Doctors of the World 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Examining how structures and systems impact migrants’ health has become increasingly important within the context of England's growing number and breadth of policies aiming to embed immigration control within public services like the NHS ( Griffiths and Yeo, 2021 ). Sharing data between the Home Office and public services (e.g., a patient's hospital bill, a victim's report of a crime, or a worker's report of employer abuse) for immigration enforcement has garnered distrust and fear within some migrant communities ( Weller et al., 2019 ; Delvino, 2020 ). Furthermore, migrants without recourse to public funds cannot receive welfare such as income support, school lunch subsidies or homelessness assistance ( Weller et al., 2020 , Delvino, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Negative media discourse around migration, community antagonism, and a hostile environment further creates a sense of unease with the potential for forced migrants to be stereotyped or discriminated against (Manstead, Reicher, Greenland, & Nightingale, 2016; Weller et al., 2019). Forced migrant families particularly value those HCPs who offered them compassion, caring concern, affection, and empathy.…”
Section: Discussionmentioning
confidence: 99%
“…The conditions prior to, during and after migration expose individuals to a range of health risks, resulting in differences in health outcomes between migrants and non-migrants in the migrant's country of arrival (2). In the UK, there are well-established multi-generational minority ethnic communities but a history of 'hostile' migration policies (3). The study of migrant health is therefore needed to complement the study of ethnic inequalities to understand how migration intersects with ethnicity, as well as its effects over and above ethnicity to shape risk factors for health, physical and mental health outcomes, and healthcare access (4).…”
Section: Introductionmentioning
confidence: 99%